Comparative Efficacy of Topical Tacrolimus 0.1% and Clobetasol Propionate 0.05% in the Treatment of Alopecia Areata (AA) : Efficacy of Tacrolimus and Clobetasol Propionate in the Treatment of Alopecia Areata - Sajjad, Danyal; Muzaffar, Bushra; Siddiqui, Muhammad Adeel; Hussain, Majid; Aslam, Sana; Farid, Huma (Pakistan Journal of Health Sciences, 2023)
Alopecia areata patients can choose from a variety of therapy methods. Each method has advantages and limitations, and its suitability varies for each patient. The medical usefulness of topical corticosteroids in AA is yet debatable. Objective: To assess the effectiveness of topical tacrolimus 0.1% vs. topical clobetasol propionate 0.05% while treating alopecia areata. Methods: Randomized-controlled trial (Double blind) conducted in Dermatology Department, CMH-Abbottabad, from November 2022 to April 2023. The seventy (70) patients with alopecia areata who attended to OPD of CMH Abbottabad between the ages of 20 and 50 were included. The non-probability consecutive sampling method was used. For up to 3 months, patients in Group A used clobetasol propionate 0.05% twice daily, while patients in Group B used topical tacrolimus 0.1% twice daily. Patients were evaluated at the start of each session, four weeks later, eight weeks later, and twelve weeks later. The SALT score was used to estimate hair loss at presentation and during the 3-month follow-up. The degree of response has been characterized by following hair re-growth as excellent (>75%), marked (51-75%), moderate (26-50%), or mild (25%). A p-value of <0.05 was considered significant. Results: When the efficacy was compared, 26 (74.3%) patients in group-A (mean age 35.23+7.87 years) shown excellent response, while 14 (40%) patients in group-B (mean age 34.29+7.87 years) with significant p-value was 0.028. Conclusions: Clobetasol propionate 0.05% was more efficacious as a therapy choice for stimulating hair re-growth in patients.